Pengaruh strategi diferensiasi terhadap loyalitas konsumen pada UD Putra TS Kabupaten Majalengka - Fatmawati, Desi; Dede Sri Rahayu (Program Studi Akuntansi IKOPIN, 2022)
UD Putra TS is a fashion business in Majalengka Regency that seeks to increase consumer loyalty for the company's long-term survival. UD Putra TS has made efforts always to increase consumer loyalty, including the differentiation strategy that UD Putra TS continuously develops to bind consumers. The problem of this research is to find out whether there is an effect of differentiation strategy on consumer loyalty. The population of this study was all consumers of UD Putra TS with a sampling technique using random sampling using the slovin formula to produce 96 people. The nature of this research is descriptive and verification. The data analysis method used is regression analysis, correlation, determination, and t-test. Based on the investigation results, there is an influence between differentiation strategy on consumer loyalty. This is evidenced by hypothesis testing using t-test so that tcount is greater than ttable (9.8724 > 1.66123). The correlation value between differentiation strategy and consumer loyalty at UD Putra TS Majalengka Regency based on the research data obtained is 0.7103. Then the relationship between the differentiation strategy variable and consumer loyalty at UD Putra TS Majalengka Regency is included in the category of a strong relationship. The contribution of differentiation strategy to consumer loyalty is 50.46%, or it can be said that the variance that occurs in the consumer loyalty variable (Y) 50.46% is determined by the variance that occurs in the differentiation strategy variable (X). The rest, amounting to 49.54%, is determined by factors outside this study. The regression equation is: Y = 1.11 + 0.41 X. This means that b is positive, namely 1.11, meaning that there is a positive effect of X on Y. The regression coefficient of 0.41 states that every increase (because b is marked +) is a 1 unit differentiation strategy that will increase consumer loyalty by 0.41 units.